2016
DOI: 10.1111/jcal.12142
|View full text |Cite
|
Sign up to set email alerts
|

Factors impacting students' online learning experience in a learner‐centred course

Abstract: Technologies bring a new era of content presentation for online teaching and learning. With more instructors adopting new tools to design online teaching materials, students are often put into learning contexts with certain new design components. Assessing learner experience and outcome in these contexts is challenging because of the complexity involved, as social and individual factors and behavioural impacts of using the new components have to be considered. Few studies have been reported in the literature i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 38 publications
3
23
0
1
Order By: Relevance
“…In all of the strands, the completer's activities were more than twice as high, except for writing posts in the forums, which was very low and not found to be significant. These results are in line with previous studies that support the assumption that engagement with various course activities and time spent in study affects learning outcome and other outcome related behaviours (Wu, ). Specifically, the findings of this research supply a comprehensive understanding of the type of engagement reflected in each student's online activity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In all of the strands, the completer's activities were more than twice as high, except for writing posts in the forums, which was very low and not found to be significant. These results are in line with previous studies that support the assumption that engagement with various course activities and time spent in study affects learning outcome and other outcome related behaviours (Wu, ). Specifically, the findings of this research supply a comprehensive understanding of the type of engagement reflected in each student's online activity.…”
Section: Discussionsupporting
confidence: 93%
“…Some researchers claim that students perceive the ease of access to varied, high quality, and up-to-date learning materials as benefiting their learning in an online course (Kahan et al, 2017;Palmer & Holt, 2010). Moreover, the course content is a significant driver in students' perception of the quality of the learning experience (Peltier, Schibrowsky, & Drago, 2007;Wu, 2016). In recent years, video is perceived as a rich and powerful medium (Chen & Sun, 2012;Ozan & Ozarslan, 2016;Zhang, Zhou, Briggs, & Nunamaker, 2006).…”
Section: Students' Engagement With Course Learning Materialsmentioning
confidence: 99%
“…Therefore, all of the activities before the class were effective as learners repeatedly reported positive insights towards the flipped tasks. Other flipped studies hinted to the effectiveness of flipped activities in growing responsibility among learners (Baepler et al, 2014;Boucher et al, 2013;Wu, 2016;Engin, 2014;Khan, 2011;Mason, et al, 2013;Wu et al, 2017;Zhai et al, 2017). Although the scope of this study was limited to upper-intermediate learners, the aforementioned instructions can be applicable to a multitude of learners with different proficiency levels.…”
Section: Discussionmentioning
confidence: 99%
“…There is a great consensus amongst the flipped users that it may result in boosting learning and expanding interactive networks via communicating the selves and exchanging ideas (Baepler, Walker & Driessen, 2014;Mason, Shuman, & Cook, 2013;Wu, 2016;Wu et al, 2017;Zhai et al, 2017). Relevant to the followers of the concept, Zhonggen and Wang (2016) by analyzing the effectiveness of flipped classroom found that flipped classroom resulted in more satisfaction and self-regulation from the part of the learners by giving more opportunities to practice their writings from wherever they could.…”
Section: Flipped Classroom Model (Fcm) In the Efl Contextmentioning
confidence: 99%
“…The new information and communication technologies are transforming the functions, roles, strategies and activities of teachers in the educational process (Ay, Karadag, and Acat 2015;Paiva, Ferreira, and Frade 2017;Wu 2016). In particular, universities are increasing the use of web applications and platforms with the purpose of creating innovative educational virtual spaces (Deschaine and Whale 2017; Kryukov and Gorin 2017;Lee 2017;Salas Rueda and Salas Silis 2018).…”
Section: Introductionmentioning
confidence: 99%